Trajectory Tracking Control Method for AUV Planar MotionBased on Three-Level Hierarchical Speed Regulation - Haonan SUN; Lei WANG (水下无人系统学报)
Autonomous undersea vehicle(AUV) often encounter the problem of track overshoot when moving underwater. To address this issue, this paper proposed a cooperative control strategy that integrated the adaptive line-of-sight guidance algorithm and the three-level hierarchical speed control architecture. In this study, the distance parameter at the end of the track was introduced into the control decision, and the dynamic allocation of the speed was achieved through a three-level hierarchical control strategy. The simulation results verify the effectiveness of the dynamic speed regulation mechanism based on the three-level hierarchical control strategy. By calculating the distance deviation between the AUV and the end of the expected track section in real time, the controller can actively implement the hierarchical deceleration strategy before the large curvature turning requirement is triggered, thereby effectively suppressing the trajectory offset phenomenon caused by momentum accumulation. Compared with the heading-speed double closed-loop algorithm, under the same trajectory, the overshoot of the method in this paper is reduced by 34.15%, enabling the AUV to still accurately travel along the predetermined trajectory when turning and significantly reducing the trajectory deviation.